Pengaruh Audit Operasional Dan Pengendalian Internal Terhadap Efektivitas Kinerja Pegawai Dinas Sosial Kota Bengkulu Tahun 2025 - Jamilah Jamilah; Pedi Riswandi; Nina Yulianasari (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
This study aims to determine the influence of operational audits and internal control on the effectiveness of employee performance at the Bengkulu City Social Service Office. \ employee performance (significance 0.014 < 0.05); (2) internal control also has a positive and significant influence (significance 0.004 < 0.05); and (3) simultaneously, both variables have a significant influence on performance (significance < 0.001). The Adjusted R² value of 0.450 indicates that 45% of the variation in employee performance can be explained by operational audit and internal control, while the remaining 55% is influenced by other factors outside the model.Based on the results, it can be concluded that the better the implementation of operational audits and the internal control system, the more increased the effectiveness of employee performance. Therefore, strengthening the monitoring system and internal control is an important factor in improving the quality of social services.